Project Based Learning: Modifying Runway Lights as Visual Landing Aids Using Solar Power - Soleh, Asep Muhamad; Parjan; Annisa Baby Callista; Ni Putu Heni Handayani; Jajang Wijaya (Universitas Pendidikan Ganesha, 2024)
The conditions found in the field of learning, namely the packaging of learning aids for understanding and creative skills, have not been handled systematically. Based on this, this study aims to analyze the differences between project-based learning models and conventional learning. The study was conducted using a quantitative method involving evaluations and student interviews. The population in this study was 8th-semester students in the Engineering Technology Study Program. The study sample amounted to 40 people. The methods used in data collection were observation, interviews, and tests. Data collection instruments used observation sheets and test questions. Data processing used the statistical data processing application of the MANOVA test. The study results showed differences in cooperation and learning outcomes between students who used the project-based learning method and those who used the conventional learning system. The project-based learning method has fostered better creativity, cooperation and learning outcomes. It was concluded that the project-based learning model can improve creativity, cooperation and student learning outcomes. This study implies that applying the project-based learning model can foster creativity and cooperation between students so that it can be used in learning.